Calcium-binding protein immunoreactivity in Gudden’s tegmental nuclei and the hippocampal formation: differential co-localization in neurons projecting to the mammillary bodies - Dillingham, Christopher M.; Holmes, Joshua D.; Wright, Nicholas F.; Erichsen, Jonathan T.; Aggleton, John P.; Vann, Seralynne D. (Frontiers in Neuroanatomy, 2015)
The principal projections to the mammillary bodies arise from just two sites, Gudden’s tegmental nuclei (dorsal and ventral nuclei) and the hippocampal formation (subiculum and pre/postsubiculum). The present study sought to compare the neurochemical properties of these mammillary body inputs in the rat, with a focus on calcium-binding proteins. Neuronal calretinin (CR) immunoreactivity was sparse in Gudden’s tegmental nuclei and showed no co-localization with neurons projecting to the mammillary bodies. In contrast, many of the ventral tegmental nucleus of Gudden cell that project to the mammillary bodies were parvalbumin (PV)-positive whereas a smaller number of mammillary inputs stained for calbindin (CB). Only a few mammillary body projection cells in the dorsal tegmental nucleus of Gudden co-localized with PV and none co-localized with CB. A very different pattern was found in the hippocampal formation. Here, a large proportion of postsubiculum cells that project to the mammillary bodies co-localized with CR, but not CB or PV. While many neurons in the dorsal and ventral subiculum projected to the mammillary bodies, these cells did not co-localize with the immunofluorescence of any of the three tested proteins. These findings highlight marked differences between hippocampal and tegmental inputs to the rat mammillary bodies as well as differences between the medial and lateral mammillary systems. These findings also indicate some conserved neurochemical properties in Gudden’s tegmental nuclei across rodents and primates.